(untitled) (Interdisciplinary Research in Education, 2022)
This paper aims to explore the perceptions of examiners in examining bachelor’s level answer sheets. This study was carried out by adopting the hermeneutic phenomenological method under a qualitative research design. The participant of the study were five teachers from the constituent campuses of Tribhuvan University.This study explored whether students mismatched the answer numbers, such as writing the incorrect answer or writing an irrelevant answer. Unpreparedness about curriculum content and writing inappropriate answers with verbal repertoire is a common problems. Most of the answer sheets were found to be lacking in managing the time while writing the answers. Furthermore, students were found poor at structuring answers and wrapping them with appropriate remarks. The study findings can contribute to the test construction, test administration, and refinement of a student’s writing with relevant content and demand for the questions.